Demonstrating the most effective interventions to improve classroom air quality. What novel in situ tests of real-world conditions show is still missing in our guidance - Donna Green; Nathan Cooper; Charitha de Silva; Prateek Bahl; Shovon Bhattacharjee; Mohamed Mahmoud Abdelkareem Mahmoud; Con Doolan; C Raina Macintyre (IOP Publishing, 2023)
Over 20 years ago a report commissioned by the European Commission identified air quality in schools as a public health priority. Despite this concern, little action was taken in the following two decades. Over the last two years as classrooms were increasingly recognised as hotspots for the transmission of SARS-CoV-2, renewed interest and resources have been made available in response to this issue. Questions remain, however, over how best to achieve safer classroom air. Our analysis assessed a range of in situ interventions to remove particulate matter (PM _2.5 ) and carbon dioxide from inside a populated classroom. Our approach used saline spray and volunteers' exhalations as our source of PM _2.5 and carbon dioxide to explore the ability of high efficiency particulate air (HEPA) filters, natural ventilation and a recirculating A/C unit to remove these air pollutants which collectively provided a novel set of data. For a total window opening of 1.86 m ^2 for a 181.7 m ^3 classroom with a HEPA filter with a 703m ^3 /hr clean air delivery rate, our results confirmed that outdoor air was needed to purge the room to reduce carbon dioxide levels that otherwise rose to >1000 ppm in 12 min. Cross and natural ventilation reduced levels of PM _2.5 and carbon dioxide very effectively-in under 5 and 10 min respectively during low levels of outside PM _2.5 . We conclude that natural ventilation supplemented with the use of HEPA filters is the most effective way to reliably improve indoor air quality year-round, balancing the need to have easy to enact approaches to reduce the buildup of PM _2.5 , airborne viruses and carbon dioxide. These results highlight an important knowledge gap. Without having localised real-time outdoor air pollution sensing, evidence-based decisions cannot be made about how often, and for how long, windows can safely remain open to purge classrooms in times of poor quality outdoor air.